2020
DOI: 10.1021/acsomega.9b04023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pot Ale from a Scottish Malt Whisky Distillery and Potential Applications

Abstract: Over 2.7 billion liters of pot ale is produced annually as a co-product of Scottish malt whisky, and apart from evaporation to pot ale syrup as a feed, it is primarily treated by anaerobic digestion or land/sea disposal. The aim of this study was to assess pot ale components and their potential applications. The insoluble solid fraction, mainly consisting of yeast, contained 55% protein, and as a protein feed ingredient, this could yield 32,400 tons of feed per annum, although the Cu content of this fraction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The possibilities of the recovery of spent grains (draff) are presented in the literature. The traditional method is the use of these by-products, either in wet or dry form, as feed (mainly for cattle or sheep), due to both its nutritional content and low cost [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The possibilities of the recovery of spent grains (draff) are presented in the literature. The traditional method is the use of these by-products, either in wet or dry form, as feed (mainly for cattle or sheep), due to both its nutritional content and low cost [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds contained in the distillery wastewater mainly come from the making process including pretreatment and hydrolysis of crops or fruits, fermentation, distillation and dehydration [9] . For effective treatment and resource recovery process of the distillery wastewater, it is necessary to identify the components in wastewater, especially the antimicrobial compounds that may affect the conventional biological treatment process and the resource recovery process for distillery wastewater via microorganisms such as microbial lipid (can be further converted to biodiesel) or biogas production from wastewater [10] , [11] , [12] .…”
Section: Additional Informationmentioning
confidence: 99%
“…The concentration of inorganic and organic fractions in pot ale varies between distilleries and their fermentation batches (Traub, 2015;McNerney, 2019). From available studies, the organic carbon fraction in pot ale is found to comprise mostly of organic acids such as acetic acid, propanoic acid and lactic acid following microbial digestion of complex non-fermentative dextrins and solubilized fibre components such as hemicellulose and lignin (White et al, 2020;McNerney, 2019). In microalgae metabolism, these organic acids can be used as carbon sources that are converted to Acetyl-CoA and other precursor compounds through various metabolic pathways which feed into the tricarboxylic acid cycle (TCA) (Falkowski and Raven, 2007;Bashan and Perez-Garcia, 2015).…”
Section: Role Of Pot Alementioning
confidence: 99%
“…Despite the high depurative efficiency achieved (<90%), effluents of pot ale still retain high organic loads with COD concentrations around 10 g L − 1 O 2 . It should be noted that the inherent variation in its composition following the distillation process makes stable anaerobic digestion difficult to maintain (Mohana et al, 2009;White et al, 2020). In some instances, the methane produced is contaminated with hydrogen sulphide, with concentrations reaching as high as 2 g L − 1 , making it an unsuitable product without further processing.…”
Section: Introductionmentioning
confidence: 99%